Comparative performance analyses of molten carbonate fuel cell-alkali metal thermal to electric converter and molten carbonate fuel cell-thermo-electric generator hybrid systems - Emin Açıkkalp; Lingen Chen; Mohammad Hossein Ahmadi (Energy Reports, 2020)
Purpose of this paper is to compare the performance of an alkali metal thermal electric converter (AMTEC) and thermoelectric generator (TEG) as a subsystem for utilizing rejected heat from the molten carbonate fuel cell (MCFC). AMTEC and TEG have various advantages such as; higher power density, no maintenance needed, silent and generally lower cost. Therefore, they have good potential to utilize waste heat. Performance parameters of systems are defined as power output density, exergy destruction rate density, energy and exergy efficiencies. Results show that the system MCFC-AMTEC hybrid system is more advantageous than the MCFC-TEG hybrid system. Some important results are listed follows; maximum power output densities for the MCFC-AMTEC and MCFC-TEG are 2425.833 (W/m2), and 1964.389 (W/m2), respectively, while efficiencies are %, 76.6% and 76.4 %.
Keywords: 330; Alkali metal electric converter; Thermoelectric generator; Molten carbonate fuel cell; Hybrid system; Performance